Global Wine Tourism: Research, Management and Marketing - Carlsen, Jack (CABI, 2014)
This is the first research-based book on wine tourism and, as such, makes a significant contribution to wine tourism research, management and marketing. Considering the emergence of wine tourism globally, and the consequent growth of academic and practitioner interest in this topic area, it is a timely publication. All of the contributed chapters in this book (apart from Chapters 1 and 20) have been double-blind reviewed prior to publication. Earlier versions of some of these chapters also appeared in the proceedings from the First International Wine Tourism Conference held in May 2004 at Margaret River, Western Australia (Carlsen and Charters, 2004). All of the contributors were required to discuss the implications of their research findings for wine tourism generally, so that practical and applied outcomes of the research could be presented. In this way, the book bridges the gap between theoretical and practical research outcomes and provides insights for academics and practitioners alike.